DEVELOPMENT OF ACADEMIC ADVISING INFORMATION SYSTEM APPLICATIONS AT MAKASSAR STATE UNIVERSITY USING THE ANDROID PLATFORM - Muhammad Rais B; Agung, Muhammad; Sa’ban Miru, Alimuddin (Journal of Electrical Engineering and Informatics, 2024)
Advising is the process where students communicate about issues that may arise during their study period. However, it is often hindered by the busy schedules and different timetables between students and their academic advisors. Therefore, a system has been developed to facilitate the advising process using the Android platform. This research adopts the Research and Development (R&D) methodology, specifically using the waterfall development model. Data collection techniques include interviews and questionnaires. The application is tested based on the ISO/IEC 25010 quality standards, covering four aspects: functional suitability, performance efficiency, usability, and portability. The functional suitability testing involved two expert professors, and 24 features were tested, indicating that the application is "Suitable" for use. Portability testing on the application was conducted by observing the output on three Android versions: Nougat, Red Velvet Cake, and Tiramisu. The results showed that the application can run on all three Android versions. Performance efficiency testing utilized the Android Profiler tool to assess CPU, memory, and network usage while running the application. The findings revealed that CPU usage was less than 50%, memory allocation was 122.2 MB, and network usage was less than 48 KB/s. Usability testing conducted by students resulted in a test score of 81.6%, categorized as "Very Good" feasibility.